EXPERT SYSTEM SELECTION OF SUPERIOR BANANA SEEDS USING FORWARD CHAINING METHOD WITH WEB APPLICATION - Adi Kiswanto (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2021)
Bananas are native to Southeast Asia. The plant of the Musaceae tribe has the Latin name Musa paradisiaca. Banana production in Indonesia is quite large, even Indonesia became one of the largest banana producers in the world. National banana production continues to increase every year, for example from 2,308,379 tons (in 1988) to 2,417,760 tons (in 1989). The largest banana-producing region is located in Java (Suhardi et al, 2002). An expert system is a computer-based system that uses knowledge, facts, and reasoning techniques to solve problems that can usually be solved only by experts in the field. Forward Chaining is a search technique that begins with known facts, then matches those facts to the sections IF of the rules IF_THEN. Based on the results of the implementation found that the application program expert system dpat facilitate the farmers in the determination of seeds of banana seeds in accordance with the criteria and this application can run well and easy in its use.